Influência de um programa de ensino de esportes coletivos de invasão na motivação e desempenho motor de escolares no ensino fundamental - Costa, Luciane Cristina Arantes da (2015)
The objective of this study was to investigate the influence of an educational team sports invasion program with the Developmental Model (MD) and the Sports Education Model (SEM) as the theoretical support on the motivation and motor performance of elementary school students. Initially, in the first articles of the thesis (Chapter 2 and 3) validation studies of the questionnaires were performed: a) Basic Psychological Needs in Exercise Scale (BPNES) and b) The Learning Climate Questionnaire (LCQ). The subjects of this study were students enrolled in elementary school in 08 public schools in the city of Maringá-PR, who were requested to test (n=403) and retest (n= 346) for the validation of the instruments. The results showed clear and relevant questions with satisfactory levels of confirmatory factorial validity and internal consistency. After that, the validated instruments (BPNES and LCQ) were used to evaluate the motivational aspects of the participants of the educational intervention program, with the use of a hybrid model (MD-MED). In Chapter 4, an autonomy, competence and relationship index of students was identified, as well as the students' perception regarding support for autonomy (learning environment) of teachers in Chapter 5. One hundred students from two public schools in the state of Paraná participated in these studies, being the groups divided into an experimental group (n=44) and a control group (CG; n=56). The analysis of the pre- and post-test data was performed after a normality verification (Kolmogorov-Smirnov); for the sample characterization, absolute and relative frequency were the employed methods; for groups comparison (EG-experimental and CG-control) non-parametric tests were utilized (Mann-Whitney "U" test or Kruskal-Wallis); the adopted level of significance was of p≤0.05. Results related to the students' motivation indicated alterations in the autonomy index, with increase for female students of the 6th grade (EG) after participating in the intervention program; no statistically significant alterations were indicated for students' relationship rates. Regarding the perception of autonomy support (learning environment), it was found that the contents pointed to the maintainability of the numbers found after the intervention program. In order to verify the motor performance of the students, in Chapter 6 the Movement Assessment Battery for Children - Second Edition (M-ABC 2) test was used. The sample consisted of 85 elementary school students (6th and 7th grades) aged 11-14 years, with 44 of them being part of the experimental group, and 41 of the control group. For data analysis, the Kolmogorov-Smirnov test was utilized to verify the normality, the Wilcoxon test to compare distinct moments (pre and post-test) and the Mann-Whitney U test to compare the groups; with the level of significance of p≤0.05. The results demonstrated that the intervention program was effective in improving the motor skills of balance, throw and catch. The results of educational intervention program in the invasion of sports teaching using the sports content (futsal, basketball and handball) were presented in Chapter 7 and 8. The program was developed in 45 classes with each group (6th and 7th grades) in a public school. For data gathering, footages of the classes and field diaries were utilized. The implementation of the hybrid model (MD-SEM) has proven to be a viable proposal, allowing the verification of perception of competence and sporting expertise, as well as motivation in sport due to technical and tactical development of students. Conducting the research on the implementation of this program was a challenging initiative and it is important to demonstrate the possibility of implementing teaching models that can help the process of teaching and learning of team sports invasion in the school environment.